2011
DOI: 10.1371/journal.pone.0017794
|View full text |Cite
|
Sign up to set email alerts
|

ShRNA-Targeted Centromere Protein A Inhibits Hepatocellular Carcinoma Growth

Abstract: BackgroundCentromere protein A (CENP-A) plays important roles in cell-cycle regulation and genetic stability. Herein, we aimed to investigate its expression pattern, clinical significance, and biological function in hepatocellular carcinoma (HCC).Methodology/Principal FindingsCENP-A expression at the mRNA and protein levels was examined in 20 pairs of fresh HCCs and corresponding nontumor liver tissues. Immunohistochemistry for CENP-A was performed on 80 paraffin-embedded HCC specimens, and the clinical signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
118
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(128 citation statements)
references
References 51 publications
(53 reference statements)
9
118
0
1
Order By: Relevance
“…This supports the hypothesis that deleted forms of HBx may contribute to liver carcinogenesis (13,(30)(31)(32). Our previous findings also demonstrated that CENP-A overexpression was correlated with serum HBsAg states in HCC patients (16). In this study, we identified a positive correlation between the expression of CENP-A immuno reactivity and the HBx COOH mutation in HCC tissues.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This supports the hypothesis that deleted forms of HBx may contribute to liver carcinogenesis (13,(30)(31)(32). Our previous findings also demonstrated that CENP-A overexpression was correlated with serum HBsAg states in HCC patients (16). In this study, we identified a positive correlation between the expression of CENP-A immuno reactivity and the HBx COOH mutation in HCC tissues.…”
Section: Discussionsupporting
confidence: 89%
“…The primary antibodies included anti-CENP-A (ab13939, 1:100, Abcam, Cambridge, UK), and anti-Hepatitis B virus X antigen (HBxAg, ab235, Abcam; 1:500). We defined that a <10% represented low, and >10% represented high levels of CENP-A expression (16).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Son çalışmalar ayrıca CENP-A'nın DNA'nın hasarlı bölgelerinde toplandığını ve çift iplik DNA kırık tamirinde yer alabileceğini düşündürmektedir. 27 CENP-A düzeyleri östrojen reseptör (ER) negatiflerde ER-pozitiflere göre yüksek bulunmuştur. Çalışmada CENP-B düzeyleri ER-pozitif ve ER-negatif tümörler arasında karşılaştırılmış, ER-pozitif ve ER-negatif tümörler arasında CENP-B düzeyin-de farklılık gözlenmemiştir.…”
Section: şEkil 41 Cenp-a Geninin 2p233 Kromozomal Lokalizasyonuunclassified